2016
DOI: 10.1177/2156587215596430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mad Honey on Some Biochemical Parameters in Rats

Abstract: The aims of this study were to determine grayanotoxin (GTX-III) toxin level in mad honey using liquid chromatography-tandem mass spectrometry and examine the dynamic changes of certain biochemical parameters in blood serum of rats that consumed mad honey. For the experimental animal study, 20 Sprague-Dawley female rats were divided into 5 groups of 4 rats each, with one group being the control group (Group 1) and the others being the experimental groups (Groups 2-5). Groups 2, 3, 4, and 5 were, respectively, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“…In similar studies previously done, Silici et al 18,19 reported that the level of GTX-III in mad honey given to experimental animals was 6.22 μg g −1 . Sahin et al 67 reported that the level of GTX-III in the mad honey given to rats was in the means of 39.94 ± 0.02 μg g −1 . Kurtoğlu et al 87 found to be GTX-I and GTX-III as 20.4 ± 1.69 μg g −1 and 8.20 ± 1.93 μg g −1 , respectively, in order to determine the GTX levels of collected mad honey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In similar studies previously done, Silici et al 18,19 reported that the level of GTX-III in mad honey given to experimental animals was 6.22 μg g −1 . Sahin et al 67 reported that the level of GTX-III in the mad honey given to rats was in the means of 39.94 ± 0.02 μg g −1 . Kurtoğlu et al 87 found to be GTX-I and GTX-III as 20.4 ± 1.69 μg g −1 and 8.20 ± 1.93 μg g −1 , respectively, in order to determine the GTX levels of collected mad honey.…”
Section: Discussionmentioning
confidence: 99%
“…The dose used was determined by taking into account the LD50 values of GTX 65,66 as well as previous studies with mad honey. 18,19,67 All mad honey applications were made directly into stomach by gavage without using vehicle. Research protocol was received the approval of Erciyes University experimental animals Ethical Board.…”
Section: Methodsmentioning
confidence: 99%
“…The MDA, CAT, SOD, and GSH-PHx activities in the blood and tissue samples have shown negative effects on the antioxidant parameters in the groups with GTx and high doses of RH (Silici & Atayoglu ). Rats that have been applied with different doses of RH for 8 days have shown an increase in liver enzymes (Sahin et al, 2015). It has been reported that RH has a hepatoprotective effect and that the R. Arboreum species decreases cholesterol and triglycerides (Prakesh et al, 2008;Verma et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Yine başka çalışmalarda, oral yolla gavaj şeklinde ya da i.p. olarak verilen grayanotoksin-III, kanda bazı biyokimyasal parametreleri belirgin şekilde artırmış ancak renal fonksiyonlarda bir bozulmaya neden olmamıştır (23)(24)(25)(26)(27) . Yakın zaman önce Türkmen ve ark.…”
Section: Introductionunclassified
“…Az sayıda deneysel çalışmada bal ekstraktı halinde hayvanlara oral, i.p. ve intraserebroventriküler gibi farklı yollarla uygulanmıştır (23)(24)(25)(26)(27)(28) . Çalışmamızda, deli bal içerisinde en fazla bulunan ve oldukça toksik olduğu bilinen grayanotoksin-III, daha önceki çalışmalardan farklı olarak i.v.…”
Section: Introductionunclassified